PENGARUH PENGETAHUAN TENTANG PENGELOLAAN KEUANGAN, OBJEKTIVITAS, PENGALAMAN KERJA, INTEGRITAS DAN MOTIVASI TERHADAP KUALITAS AUDIT (Studi Pada Inspektorat Di Kabupaten/kota Di Provinsi Riau) - Safitri, Meilina; Azlina, Nur; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to determine (1) influence of knowledge of financial management on audit quality, (2) influence of objectivity on audit quality, (3) influence of working experiences on audit quality, (4) influence of integrity on audit quality, and (5) influence of motivation on audit quality. Samples from this study is the auditor who worked in inspectorate regencies/cities in riau, exactly in Bengkalis, Kuantan Singingi, and Pekanbaru. Data were analyzed using multiple regression analysis using SPSS version 21. The data used are primary data using questionnaires. The analysis technique used to test hypotheses is random sampling. The results showed that knowledge of financial management, working experiences, integrity and motivation didn’t influenced audit quality. Beside that, this study proved that objectivity influenced audit quality. The test results obtained R2 values of 0,602 which means 60,2% of variables that affect the audit quality could be explained by the independent variables in this study, while the remaining 39,8% is explained by variables outside the model. For future research, I suggest to extend survey area coverage and add more variable that can influence audit quality.Keywords : Knowledge Of Financial Management, Objectivity, Working Experiences, Integrity, Motivation, and Audit Quality